Business plan for noodle manufacturing business / Norsharmimi Ahmad - Ahmad, Norsharmimi (2017)
Noodles are becoming another sources of stapled food in Asian countries including our country Malaysia even as Continental and Italian delicacy. Noodles are can be made from wheat, rice and other raw material such as starch. Wheat noodles are produced mainly from flour, water and salt, and the process of noodles production include dough mixing, sheeting, combining of sheets, resting, rolling and cutting, followed by different processing treatments.